Effects of αTAT1 and HDAC5 on axonal regeneration in adult neurons - Lin, Shen; Sterling, Noelle A.; Junker, Ian P.; Helm, Courtney T.; Smith, George M. (PloS one, 2017)
The role of posttranslational modifications in axonal injury and regeneration has been widely studied but there has been little consensus over the mechanism by which each modification affects adult axonal growth. Acetylation is known to play an important role in a variety of neuronal functions and its homeostasis is controlled by two enzyme families: the Histone Deacetylases (HDACs) and Histone Acetyl Transferases (HATs). Recent studies show that HDAC5 deacetylates microtubules in the axonal cytoplasm as part of an injury-induced regeneration response, but little is known about how acetylation of microtubules plays a role. Alpha-tubulin acetyl transferase (αTAT1) is a microtubule specific acetyl transferase that binds to microtubules and directly affects microtubule stability in cells. We hypothesize that increasing tubulin acetylation may play an important role in increasing the rate of axonal growth. In this study, we infected cultured adult DRG neurons with αTAT1 and αTAT1-D157N, a catalytically inactive mutant, and HDAC5, using lentiviruses. We found that αTAT1 significantly increases tubulin acetylation in 293T cells and DRG neurons but αTAT1-D157N does not. Furthermore, in neurons infected with αTAT1, a significant increase in acetylated tubulin was detected towards the distal portion of the axon but this increase was not detected in neurons infected with αTAT1-D157N. However, we found a significant increase in axon lengths of DRG neurons after αTAT1 and αTAT1-D157N infection, but no effect on axon lengths after infection with HDAC5. Our results suggest that while αTAT1 may play a role in axon growth in vitro, the increase is not directly due to acetylation of axonal microtubules. Our results also show that HDAC5 overexpression in the axonal cytoplasm does not play a crucial role in axonal regeneration of cultured DRG neurons. We expressed these genes in DRG neurons in adult rats and performed a sciatic nerve crush. We found that axons did not regenerate any better when infected with any of the constructs compared with control animals. Thus, while αTAT1 may be important for axonal growth in vitro, neither αTAT1 nor HDAC5 had an effect in vivo on the regeneration of sciatic nerves.